An empirical study on application and efficiency of gridded management in public service supply of Chinese Government. Issue 1 (13th March 2017) - XiuYin, Bai; Hanif, Muhammad Imran; Fensheng, Li; Hanif, Muhammad Shehzad; Yinhua, Gu
Abstract : Purpose: Gridded management in the public service supply is still in the experience exploratory stage, and this paper aims to analyze the inherent logic and operation mode of the gridding mechanism of the public supply based on the existing theory study and practices, and verify its efficiency so as to come to the conclusion whether it could be promoted to a wider range. Design/methodology/approach: The methodology applied in this paper was case study/deductive induction. Findings: The grid model in the public service supply needs to be demonstrated completely in theoretical logic and operation principles before it is promoted across the country. Meanwhile, full support of the government is required in terms of service concept, function distribution, technical parameters and infrastructure. Research limitations/implications: The inherent logic and operation mode of the gridding mechanism of the public service supply needs enough practice tests. The practical test of efficiency analysis of the gridding mechanism of the public service supply is not enough. Social implications: This paper validated whether the gridding mechanism that originated from China's urban management can be promoted to all over the country in the public service supply. It provides references for government policy. Originality/value: This paper constructs a gridded management model for public service provision in urban and rural areas on the basis of an analysis of the plight of traditional model of public service provision, thus delivering the same standard of public service for both urban and rural areas through optimization of resource allocation without requiring more supply and fundamental change to the content of service.